The Influence of Financial Literacy Skills on The Investment Interest of Students of The Faculty of Economics and Business, University of Muhammadiyah Makassar - Khaedar Sahib, Muhammad; Anggoro KR , M. Yusuf Alfian Rendra Anggoro KR (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Financial Literacy is the ability to understand and apply various financial skills This study aims to find out 1) an overview of financial literacy skills of students of the Faculty of Economics and Business, University of Muhammadiyah Makassar, 2) an overview of investment interests of students of the Faculty of Economics and Business, University of Muhammadiyah Makassar, 3) the influence of financial literacy skills on the investment interests of students of the Faculty of Economics and Business, University of Muhammadiyah Makassar. The population in this study is all students of the Faculty of Economics and Business, University of Muhammadiyah Makassar with a total of 5043 people and by applying the slovin formula (10%) obtained a sample of 98 students who then used proportional random sampling techniques in obtaining them. The data collection technique used is a Liquet scale questionnaire which in the development of instruments on each variable will be tested for content validity using the Gregory formula, construct validity testing using confirmatory factor analysis (CFA) analysis and instrument reliability testing using the alpha conbach formula. The data analysis techniques used are descriptive statistics and simple linear regression statistics. The results revealed that 1) the picture of student financial literacy skills in general is in the high category, ) the picture of student investment interest is generally in the low category, 3) there is a positive and significant influence of financial literacy skills on the investment interest of students of the Faculty of Economics and Business, University of Muhammadiyah Makassar. The magnitude of the influence of financial literacy skills on student investment interest is 57%.